Does Financial Efficiency Reflect Government Performance? Evidence from Indonesian Provinces - Helvy Tiana Rosa; Loggar Bhilawa (Universitas Negeri Semarang, 2025)
Purpose: The study critically examines whether financial efficiency ratios in local government financial reports genuinely reflect government performance or primarily indicate fiscal compliance. Within Indonesia’s decentralized governance framework, we investigate the relationship between expenditure realization, environmental outcomes, and reported financial efficiency. Method: An explanatory quantitative approach was utilized, employing balanced panel data from 34 provinces in Indonesia from 2020 to 2023. Financial performance was measured using the efficiency ratio. Regional expenditure was assessed using the expenditure realization ratio, and environmental performance was evaluated using the Environmental Quality Index (EQI). Total revenue was accounted for as a control variable. Panel regression analysis was conducted, and the appropriate estimation model was identified using the Chow and Hausman tests. Findings: Regional expenditure significantly predicts financial efficiency, confirming the ratio’s mechanical sensitivity to budget execution. However, environmental performance shows no significant association with financial efficiency, while fiscal capacity demonstrates a strong negative relationship. The limited explanatory power suggests efficiency ratios primarily capture fiscal compliance rather than substantive policy outcomes. Novelty: The study provides empirical evidence by comparing accounting-based financial efficiency indicators with outcome-based environmental performance measures, demonstrating that financial efficiency ratios primarily reflect fiscal compliance rather than substantive policy outcomes.